SMART SILICON SENSOR – MAGNETIC COMPASS ON THE BASE OF A 3-D HALL STRUCTURE - Dimitrov, Konstantin (International Journal of Computing, 2014)
In this paper is discussed some of the trends in the industrial designs of smart sensor systems. High performance sensor systems have been implemented by combining the sensing and signal processing functions on the same chip. A very promising magnetic compass for Earth magnetic field measurement is created on the base of a 3-D Hall structure.